Enrichment of sialylated IgG by lectin fractionation does not enhance the efficacy of immunoglobulin G in a murine model of immune thrombocytopenia. - Theresa Guhr (Public Library of Science (PLoS), 2011)
Intravenous immunoglobulin G (IVIg) is widely used against a range of clinical symptoms. For its use in immune modulating therapies such as treatment of immune thrombocytopenic purpura high doses of IVIg are required. It has been suggested that only a fraction of IVIg causes this anti immune modulating effect. Recent studies indicated that this fraction is the Fc-sialylated IgG fraction. The aim of our study was to determine the efficacy of IVIg enriched for sialylated IgG (IVIg-SA⁺) in a murine model of passive immune thrombocytopenia (PIT). We enriched IVIg for sialylated IgG by Sambucus nigra agglutinin (SNA) lectin fractionation and determined the degree of sialylation. Analysis of IVIg-SA⁺ using a lectin-based ELISA revealed that we enriched predominantly for Fab-sialylated IgG, whereas we did not find an increase in Fc-sialylated IgG. Mass spectrometric analysis confirmed that Fc sialylation did not change after SNA lectin fractionation. The efficacy of sialylated IgG was measured by administering IVIg or IVIg-SA⁺ 24 hours prior to an injection of a rat anti-mouse platelet mAb. We found an 85% decrease in platelet count after injection of an anti-platelet mAb, which was reduced to a 70% decrease by injecting IVIg (p<0.01). In contrast, IVIg-SA⁺ had no effect on the platelet count. Serum levels of IVIg and IVIg-SA⁺ were similar, ruling out enhanced IgG clearance as a possible explanation. Our results indicate that SNA lectin fractionation is not a suitable method to enrich IVIg for Fc-sialylated IgG. The use of IVIg enriched for Fab-sialylated IgG abolishes the efficacy of IVIg in the murine PIT model.